Leveraging the EPICS Environment to Enhance Design Skills in Electronics Engineering Students: A Continuous Improvement Approach under ABET Accreditation - G, Mauricio Pardo; R, Jesus D. Ariza; M, Jose A. Giraldo (Conference proceedings (IEEE Colombian Conference on Communications and Computing. Online), 2024)
This paper explores how the Electronics Engineering program at Universidad del Norte integrates the EPICS framework to enhance student learning and meet ABET accreditation standards. The curriculum blends foundational design principles with iterative processes and real-world constraints, focusing on practical application and technical skills. Collaboration with Purdue University has introduced a Mini-EPICS program in courses such as Analog Electronics II and III, promoting early engagement in design and project management. Initial out-comes highlight significant gains in student skills, particularly in problem-solving, teamwork, and practical design. Continuous assessment based on feedback ensures alignment with accreditation standards and educational goals, preparing students for professional practice and driving curriculum enhancements. This positions Uninorte at the forefront of electronics engineering education.